Essential Facilities Doctrine Untuk Membatasi Hak Eksklusif Paten - Pramoediyanto, Fidyani Leirta (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2020)
This study aimed to discuss the exclusive rights of patents and the efforts to limit them through freedom of fair business competition. The study used normative legal research methods with a statutory approach and a conceptual approach. Data analysis was descriptive analysis. The results showed that the exclusive rights in patents were limited by several provisions to eliminate fair business competition. An exclusive right to a patent owner was a patent right was to use the patent and prohibits other parties from using, producing, distributing, selling, leasing or otherwise without the permission of the patent owner. Patents were limited to a period of 20 years after which they could be used by the public. Restrictions on patents as intellectual property by considering account aspects of public interest, public order, morals and religious morals. The essential facilities for doctrine were one of the efforts to overcome the abuse of exclusive rights, namely by requiring business actors to give opportunities to their competitors to use these important facilities owned by patent holders.